High stakes : a novel - Steel, Danielle (New York : Delacorte Press, 2022)
"Five women work together at a boutique literary and talent agency while the challenges of their individual lives causes chaos both inside and outside the office." --
Keywords: Publishers and publishing -- Fiction; Talent scouts -- Fiction; New York (N.Y.) -- Fiction; Domestic fiction; Thrillers (Fiction)